Os movimentos insurgentes e o patrimônio: o surgimento do Espaço Comum Luiz Estrela em Belo Horizonte, Minas Gerais - Liliane Augusta Moreira (2018)
The recent movements of urban occupation in Brazil, coming mainly from a broad process of insurgencies, global, served to trigger discussions potent linked to the right to the city. In the field of cultural heritage, this aspect appears influenced by the negligence of the State in the care of your property's architectural, historical, and cultural. In this respect then, elucidates in this work the emergence of the occupation of the cultural Espaço Comum Luiz Estrela in the city of Belo Horizonte, an initiative that inspired by the ideals propagated during the Protests of June 2013 brought together a broad group of individuals who articulated under anarchist principles such as self-management and horizontality they decided to occupy a property listed in a deplorable state of conservation. The place occupied, the house of the Street of Manaus, built to be a Military Hospital in 1913 whose trajectory was still several uses, including being a hospital for neuropsychiatry of children. Attentive to the memory of the place,the activists articulated in the collective process of the restoration of the site occupied, a measure that is anchored in the recommendation of the constitutional of the function of the preservation of cultural assets should be exercised by the whole society. Thus, we discuss the uniqueness of this action, highlighting the importance of the movements of insurgents in the preservation of properties of historical and architectural listed.